Work Meaning and the Flexibility Puzzle - Thimo De Schouwer; Iris Kesternich (CESifo GmbH, 2024)
We study heterogeneity in the prevalence of and preferences for workplace flexibility and work meaning. We show that, internationally, women and parents value flexibility more but do not work more flexible jobs. The gender dimension of this flexibility puzzle is related to differences in meaningful work, which women value higher and sort into, at a significant price corresponding to 20 to 70% less flexibility. The parental dimension is connected to preferences for meaning and flexibility diverging after childbirth. We show through counterfactuals that making meaningful jobs more flexible reduces the gender gap in total compensation by almost a quarter.
Keywords: D91; J16; J31; 330; work meaning; workplace flexibility; gender; inequality; choice experiment